Early Intervention as a Part of Support System for Children with ASD and Their Families in Perm Region - V.A. Bronnikov; M.I. Grigoreva; N.G. Vaytulevichyus; V.Y. Serebryakova (Moscow State University of Psychology and Education, 2022)
The number of children with autism spectrum disorders (ASD) and other mental disorders is increasing in the Perm Region. Currently, services for children with ASD are provided by organizations and institutions of the health, edu- cation and social services system; non-profit organizations provide support to families. The need for the development of a system of integrated support of individuals with ASD becomes more and more urgent. Technology of providing early comprehensive intervention to children with ASD and their families in the State Budgetary Institution of the Perm Region «Center for Complex Rehabilitation of Individuals with Disabiilties» is designed as a 6-month course, which includes ADOS differential diagnostic tool, M-CHAT screening test, Early Start Denver Model. Early in- tervention is seen as an essential first step in the comprehensive support to children with ASD. Further steps of the development of complex support system to children with ASD and their families in Perm Krai on the basis of creation of system of interdepartmental interaction are presented.